The Threefold Logic of Integrating Digital Intelligence Technology into the Construction of Chinese Mainstream Ideology - Guanghuan Gao (Studies in Social Science & Humanities, 2024)
In the era of digital intelligence, the construction of Chinese mainstream ideology faces new opportunities and challenges, which can be further explored through theoretical analysis, practical application, and real-life experiences. From a theoretical perspective, Marxism’s examination of the relationship between science, technology, and ideology along with Frankfurt School’s theory on science and technology ideology serve as valuable references. In terms of reality, integrating digital intelligence technology into China’s ideological construction is both feasible and necessary. Moreover, there exists a mutual need between digital intelligence technology and China’s ideological construction. As for practice, we can focus on strengthening party leadership, emphasizing value guidance, optimizing system design, improving legal frameworks to illuminate the path towards integrating digital intelligence technology into the development of China’s mainstream ideology.